The Effect Of Training And Work Environment On The Performance Of Warehouse Employees At PT Shopee Internationalindonesia Bekasi Branch - Trianto, Subur; Priatna, Isep Amas (Pascasarjana Universitas Pasundan, 2025)
This research aims to determine the partial and simultaneous influence of training and work environment on employee performance warehouse PT Shopee International Indonesia Bekasi Branch. The method used in this research is quantitative with a descriptive associative approach and a saturated sampling technique with a population and sample of 56 respondents. The analytical methods used include linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and Hypothesis Testing as a means of proving the hypothesis. The correlation coefficient between training and work environment on employee performance is at the level of 0.816, so the level of correlation between variables is defined as strong. Hypothesis testing obtained a value of 0.000 < 0.05 thus showing that there is a partially positive and insignificant influence between the work environment on employee performance at PT Shopee International Indonesia Bekasi Branch. The results of this research are training (X1) and work environment (X2) with the regression equation Y = 7.022 + 0.224X1 + 0.570X2 which can be interpreted as training and the work environment having a positive effect on employee performance. Partial or simultaneous hypothesis testing obtained fcount > ftable (53,430 > 3.17) and significant < 0.05 (0.000 < 0.05), so Ho3 is rejected and Ha3 is accepted, meaning that training (X1) and work environment (X2) have a positive and insignificant effect on employee performance. The results of the Determination coefficient analysis which were tested together had an influence of 0.656 or 65.6% while the remaining 34.4% was influenced by other factors.